Compressive and Flexural Properties of the Kevlar Fiber as a Textile-Reinforced Concrete for Lightweight Construction Applications - Hendra; Syahla Andini Putri; Muhammad Arief Herdianto (Journal of the Civil Engineering Forum, 2025)
Textile-reinforced concrete (TRC) offers a sustainable alternative to conventional steel-reinforced concrete by incorporating textile elements, thereby reducing carbon emissions and enhancing design flexibility. This study examines the use of Kevlar fiber reinforcement in improving the mechanical performance of concrete, with particular attention to compressive and flexural properties. Three Kevlar reinforcement configurations were evaluated: 3-dimensional (3D) rebar, 3D hollow woven fabric, and solid 3D woven fabric, alongside a control sample of unreinforced concrete. Compression tests were conducted in accordance with SNI 03-1974 1990, which is broadly equivalent to ASTM C39 in terms of loading procedure and specimen dimensions. Results showed that the 3D rebar configuration achieved the highest compressive strength of 14.31 MPa, marginally exceeding that of the unreinforced control at 13.28 MPa. Although the gains in compressive strength were modest, the flexural performance exhibited substantial improvement. Flexural tests, following ASTM C78 standards, revealed that the solid 3D woven fabric configuration achieved a flexural strength of 12.17 MPa, whereas that of unreinforced sample was 3.65 MPa. These results indicate that Kevlar-reinforced TRC can be particularly advantageous for applications where superior flexural capacity is required, even if compressive strength remains at a moderate level. Potential uses include non-structural or secondary lightweight elements, such as canopies, facade panels, and other architectural components where weight reduction, crack resistance, and design adaptability are desirable. The findings also highlight the influence of reinforcement configuration, with the solid 3D woven fabric providing the most significant flexural benefits. This research contributes to the growing body of evidence supporting the viability of synthetic fiber reinforcement, such as Kevlar, in sustainable concrete design and construction.